Online brand communities: when consumers are negatively engaged - Bilro, R. G. (2019)
The goal of the current research is to explore the influence of negative engagement on committing participants in hate online brand communities. To reach this aim, three brands are used to assess this phenomenon (Starbucks, Apple, and McDonald’s), and three related hate online brand communities of such brands are involved. An online questionnaire is developed based on previously validated scales and fulfilled by 300 online members of mentioned communities. Findings reveal the importance of Brand influence, Helping, and Self-expression dimensions on participants to be committed to hating brand communities.